How to Write a Dynamic Lesson Plan？ -Basis of Ignatian Pedagogical Paradigm (Global Journal of Human-Social Science, 2020)
Future education should not allow teachers to become the "protagonist" of the classroom. It should stimulate students' self-efficacy, make students the "protagonist" of the schoolroom, and apply the knowledge they have learned in real life. This article proposes the Ignatian Pedagogical Paradigm (IPP) introspective teaching method, which first, explains what the IPP is to apply this dynamic in the classroom; secondly, why the active lesson base on the IPP; finally, how to prepare the energetic lesson plan.
Keywords: teachers; students; reflection; lesson plan; teaching philosophy